Prioritization of patients for germline testing based on tumor profiling of hematopoietic malignancies - Godley, Lucy A. (Frontiers in Oncology, 2023)
Germline predisposition to hematopoietic malignancies is more common than previously appreciated, with several clinical guidelines advocating for cancer risk testing in an expanding pool of patients. As molecular profiling of tumor cells becomes a standard practice for prognostication and defining options for targeted therapies, recognition that germline variants are present in all cells and can be identified by such testing becomes paramount. Although not to be substituted for proper germline cancer risk testing, tumor-based profiling can help prioritize DNA variants likely to be of germline origin, especially when they are present on sequential samples and persist into remission. Performing germline genetic testing as early during patient work-up as possible allows time to plan allogeneic stem cell transplantation using appropriate donors and optimize post-transplant prophylaxis. Health care providers need to be attentive to the differences between molecular profiling of tumor cells and germline genetic testing regarding ideal sample types, platform designs, capabilities, and limitations, to allow testing data to be interpreted as comprehensively as possible. The myriad of mutation types and growing number of genes involved in germline predisposition to hematopoietic malignancies make reliance on detection of deleterious alleles using tumor-based testing alone very difficult and makes understanding how to ensure adequate testing of appropriate patients paramount.